2018
DOI: 10.14812/cuefd.293221
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Loneliness in Turkish University Students: Shyness and Gender

Abstract: The purpose of the study was to investigate how well shyness and gender predicted loneliness levels of university students. The UCLA Loneliness Scale, the Cheek and Buss Revised Shyness Scale and a personal information sheet were used to collect data. The sample of the study was 375 (242 female, 133 male) university students from different departments of a state university in Turkey. Multiple Regression Analysis was used to analyze the data. The results showed that the regression model containing shyness and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Henderson et al 14 found that shyness under the influence of social anxiety includes uncontrolled emotions and loneliness. Muyan-Yilik et al 39 found that loneliness has a two-way relationship with shyness in students. Tan et al concluded that loneliness and reduced social suport relationships can lead to shyness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Henderson et al 14 found that shyness under the influence of social anxiety includes uncontrolled emotions and loneliness. Muyan-Yilik et al 39 found that loneliness has a two-way relationship with shyness in students. Tan et al concluded that loneliness and reduced social suport relationships can lead to shyness.…”
Section: Discussionmentioning
confidence: 99%
“…4 Zhong et al 38 found a significant relationship between alexithymia and social support, social interactions and lack of shyness among nurses. Muyan-Yilik et al 39 found that loneliness has a two-way relationship with shyness in students. Zhao et al 40 found a significant relationship between emotional intelligence and loneliness with shyness.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding family related factors, a relationship has been found with the interaction with parents in their positive communication and time together (Majorano et al, 2017), with family cohesion and adaptability (Fujimori et al, 2017), and with stress in the academic context (Stoliker and Lafreniere, 2015). Finally, in the intra and interpersonal dimensions, it has been associated with shyness (Bian and Leung, 2015;Muyan et al, 2018), avoidance (Demirli and Demir, 2014), anxiety to speak (Odaci and Kalkan, 2010), and self-esteem (Chiao et al, 2019). On the other hand, loneliness has a mediating effect on the relationship between excessive use of social networks and real-life social interaction in university students (Ndasauka et al, 2016), as well as on the relationship between social skills and depressive and anxious symptoms (Moeller and Seehuus, 2019).…”
Section: Introduction Lonelinessmentioning
confidence: 99%